Pengaruh Earning Per Share, Net Profit Margin, Free Cash Flow dan Likuiditas Terhadap Kebijakan Dividen pada Perusahaan yang Terdaftar di Jakarta Islamic Index (JII) Periode 2016-2018 - Nita Astuti (Jurnal Pasar Modal dan Bisnis, 2020)
This study aims to test and analyze empirically the effect of earnings per share, net profit margin, free cash flow and liquidity on dividend policy. The objects in this study are companies that are consistently listed on the Jakarta Islamic Index (JII) for the 2016-2018 period. The research sample of 13 companies obtained by purposive sampling technique. The research data is secondary data obtained from the Indonesia Stock Exchange (BEI). Data analysis using panel data regression analysis. Data processing in this study uses the E-Views 9 program. The results of this study indicate that net profit margin, free cash flow and liquidity have an effect on dividend policy. Meanwhile, earnings per share has no effect on dividend policy. Overall, the independent variables simultaneously influence dividend policy.